Computational modeling and conjugate heat transfer study for in situ design of artificial porous media at varied orientations. (2022) - Prajapati, Shivam; Chharia, Aviral; Mehta, Nishi; Yadav, Shulabh
Abstract: Computational modeling and design of artificial porous media has gained immense attention in recent years due to its numerous applications, particularly in the biomedical and electrical industries. Conjugate heat transfer study of porous media in an enclosure is performed in several applications to study generated heat dissipation. The present work investigates the characteristics of conjugate heat transfer on various orientations of computationally modeled artificial porous media structure. In the study, the rate of heat transfer is compared for horizontal and vertical orientations of the porous structures which mainly consists of holes and pores. The study also investigates the effect of porosity on heat transfer. Furthermore, the study establishes that for both horizontal and vertical orientations, an increase in porosity results in an increase of the heat transfer rate from the porous media. The work also discusses, the heat transfer occurring due to forced convection in porous structures. Also, we considered a range of velocities from 1 m/s to 4.5 m/s for analyzing the effect of flow rate on the average heat flux.